Effects of Different Compost on Vegetative and Yield Performance of Pea. Issue 17 (25th September 2022) - Chaudhary, Neelam; Singh, Chandan; Pathak, Priya; Vyas, Deepak
ABSTRACT: The present study deals with the effects of Biosolid (animal manure), Spent Mushroom Compost (SMC), and Leaf Compost on the vegetative growth and yield of pea ( Pisum sativum L.). We have examined the physicochemical properties and fungal flora of soil (control) and different composts (amendments). The composts (amendments) were taken in four concentrations, i.e., 25, 50, 75, and 100%, along with complete loam soil as a control. The result reveals the differential response of compost (amendments), showing that Biosolid gives a higher yield at 25%, whereas SMC with 50% and Leaf compost best results at 75% concentrations, respectively. The other parameters of the test plant, such as height, numbers of leaflets, numbers of pods, 100 seeds weight, are found in accordance with respective yields in all the amendments. However, SMC found better fertilizers compared to other test organic substances.